Ciri Khas Gaya Desain Indische pada Gereja-Gereja di Jawa Timur dan Jawa Tengah - Rosalina Christine Prasetio (Intra, 2016)
East and Central Java are provinces with vast region in Java Island and high population level, which allow the acculturation to develop, especially Colonial Building, as evidence of Dutch Colonial history relic. One of the famous design style at the moment was indische which is a mixture of Javanese and European culture. Finding similarities and differences that exist in today’s church with descriptive comparative method and the selection of buildings based on stratified sampling technique, samples are grouped by function of the building. Writer found that indische design style characteristics in colonial buildings, which is the church in East and Central Java is the plastered wall and white paint. The floor use terrazzo materials and granite with a geometric and tendrils pattern. The wall use thick bricks, painted in plain white. Using hanging accessory on the wall, alternating between windows and walls. It has high ceiling painted in plain white.